The Influence of Internal Locus of Control and Academic Self-Efficacy on School Well-Being in Students - Febriyanto, Febriyanto; Finansiya, Ananta; Tarigan, Beby Astri; Hartini, Sri; Safarina, Nur Afni (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to determine the influence of Internal Locus of Control and Academic Self-Efficacy on School Well-Being in SMA Global Prima Medan students. This quantitative research involved 127 students as a sample using the Proportionate Stratified Random Sampling method. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 24. The assumption test includes normality, multicollinearity, and autocorrelation. The study's results stated that Internal Locus of Control and Academic Self-Efficacy influenced School Well-Being with a value of F = 342.966 and p = 0.001 (p<0.05). The results showed that Internal Locus of Control (? = 0.718, p = 0.001) and Academic Self-Efficacy (? = 0.190, p = 0.001) significantly and positively affected School Well-Being, with a contribution of 84.4%. Other factors influenced the remaining 15.6%. These findings provide a solid foundation for developing more effective educational practices. Schools can take advantage of the results of this research by designing programs that aim to improve students' internal locus of control and academic self-efficacy, such as self-development training that focuses on forming positive mindsets, stress management, and decision-making skills. This study concludes that Internal Locus of Control and Academic Self-Efficacy affect School Well-Being.